Together We Are Stronger: Examining Virtual Leadership Behavior Towards Knowledge Sharing in Online Programming Communities - Al-Mashhadani, Abdulrazak F.Shahatha; Ahmad, Rahayu; Yahya, Noor Izzah (2018)
Online communities are rapidly growing as an outlet for social support and community building. However, very few succeeded in inspiring members to share their knowledge. The problem of under contribution in online settings has triggered researchers to investigate the role of virtual leadership in promoting knowledge sharing. Using path-goal theory, this study examines the role of supportive, participative, and achievement-oriented leadership towards knowledge sharing in online programming communities. Data were collected from 20 online programming communities and used to empirically test the proposed model. The result from the structural equation modelling suggests that the three leadership behaviors significantly moderate the effect of self-efficacy and outcome expectancy towards members’ knowledge sharing in the online programming community. A suitable level of autonomy and recognition of members contributions can motivate members to continuously contribute to online programming communities and help promote sustainability in this platform.